Photodynamic inactivation of Streptococcus mutans and Streptococcus sanguinis biofilms in vitro - Pereira, Cristiane Aparecida [UNESP]; Costa, Anna Carolina Borges Pereira [UNESP]; Carreira, Claudia Moura; Junqueira, Juliana Campos [UNESP]; Jorge, Antonio Olavo Cardoso [UNESP] (Springer Nature, 2013)
The purpose of this study was to evaluate specific effects of photodynamic inactivation (PDI) using erythrosine (ER) and Rose Bengal (RB) photosensitizers and a blue light-emitting diode (LED) on the viability of Streptococcus mutans and Streptococcus sanguinis biofilms. Biofilms were grown in acrylic disks immersed in broth to production of biofilms, inoculated with microbial suspension (106 cells/mL) and incubated for 48 h. After the formation of biofilms, the effects of the photosensitizers ER and RB at a concentration of 5 μM for 5 min and blue LED (455 ± 20 nm) for 180 s, photosensitizers alone and conjugated were evaluated. Next, the disks were placed in tubes with sterile physiological solution (0.9 % sodium chloride) and sonicated for to disperse the biofilms. Tenfold serial dilutions were carried and aliquots seeded in brain heart infusion agar which were then incubated for 48 h. Then the numbers colony-forming units per milliliter (CFU/mL; log 10) were counted and analyzed statistically (ANOVA, Tukey test, P ≤ 0.05). Significant decreases in the viability of all microorganisms were observed for biofilms exposed to PDI mediated by both photosensitizers. The reductions with RB and ER were, 0.62 and 0.52 log10 CFU mL -1 for S. mutans biofilms (p = 0.001), and 0.95 and 0.88 log 10 CFU mL-1 for S. sanguinis biofilms (p = 0.001), respectively. The results showed that biofilms formed in vitro by S. mutans and S. sanguinis, were sensitive to PDI using a blue LED associated with photosensitizers ER or RB, indicating its use in the control of caries and periodontal diseases. © 2012 Springer-Verlag London Ltd.
Keywords: Biofilm; Photodynamic inactivation; Streptococccus sanguinis; Streptococcus mutans; agar; erythrosine; photosensitizing agent; rose bengal; bacterial count; bacterial viability; bacterium culture; biofilm; blue light; colony forming unit; controlled study; dilution; in vitro study; light emitting diode; nonhuman; photodynamic inactivation; photodynamics; priority journal; reduction; Streptococcus sanguinis; suspension cell culture; ultrasound